Rethinking Economic Security in a Precarious World. (July 2020) - Parfitt, Claire; Barnes, Tom
The introduction to this special issue of Critical Sociology offers an interpretation of recent debates in the precarity literature and the role precarity plays in a wide range of disciplines' scholarship. It makes the case for a broad conceptualization of precarity, one that recognises many dimensions and sites of precariousness in contemporary life. In addition to providing grounded examples of precarity experienced in this broad sense, this collection of articles focuses on responses to precarity and strategies that individuals, collectives and institutions are taking to address an increasingly precarious life. The collection focuses on Australia, where the authors are based. This affords readers an opportunity to observe the particularities of precarity in Australia, where some elements of the neoliberal welfare state have cushioned, and others have sharpened, people's experience of volatility and uncertainty.